(3TQM ebOeI GdbdGFO aj JUMjM GdYbGFOs - (3YHO Gddg Hf eMeO Hf CHj GdbGSe GdRjOj GdYHSj GdfLQj, GdfLQj,J (B877 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdJhMjO s
(3BNQgG (B:s
(3jfJgi HaUd ai GdOGQ hCMcGegG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B272s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdJhMjO hGdedd hGdfMds